ASPECTOS ECOLÓGICOS DE LAS CECIDIAS DE BACCHARIS LINEARIS (R. et P.) PERS., EN CHILE CENTRAL - Sáiz, Francisco; Castro, Carolina (Acta Entomológica Chilena, 2022)
In the National Park La Campana, sector Palmas de Ocoa (32°55’ S, 71°55’ W), some ecological aspects of galls developed on Baccharis linearis were studied throughout a phenological cycle of the plant. The following aspects were analyzed: general morphology of cecidia (shape, size, color), morphological change of gall, biological aspects of gall-makers and parasitoids and relationships between the life cycle of gall-makers insects and the phenology of plant. Eight different kinds of galls were detected and described, six on twigs and two on leaves, three of which were described for the first time. Four types of galls analyzed were induced by Cecidomyiidae (Díptera), two by Psylloidea (Hemiptera), one by Lepidoptera and one by Eriophyidae (Acari).